Analisis Yuridis Prasyarat Pembentukan Tim Seleksi KPU dan BAWASLU Tahun 2022 Perspektif Siyasah Dusturiyah - Fizay Muhamad Faozan (SIYASI: Jurnal Trias Politica, 2023)
The Presidential Decree Number 120/P of 2021 regarding the formation of the selection team for candidates of KPU and Bawaslu for the period of 2022-2027 is not in accordance with Article 22 Paragraph 3 of Law Number 7 of 2017. Article 22 Paragraph 3 stipulates that the composition of the selection team for candidates of KPU/Bawaslu consists of 3 government officials, 4 academics, and 4 members of the public. The findings of this study state that: 1) The formation of the selection team for candidates of KPU and Bawaslu for the period of 2022-2027 is not in accordance with one of the requirements in Law Number 7 of 2017 concerning elections, namely Article 22 Paragraph 3; 2) The impact of all decisions made by the selection team can be considered illegal because they are not in accordance with the applicable law, and the selection results can be declared null and void. Furthermore, the composition of the selection team can cause conflicts of interest; 3) The review of Siyasah Dusturiyah, in accordance with Surah An-Nisa Verse 58 and the principle that "the policy of a leader depends on the benefit", indicates that the composition of the selection team should be based on the benefit, acting fairly and responsibly in accordance with the constitution so that no citizen's rights are violated.